Addition of Exogenous Fibrolytic Enzymes to Lactating Dairy Cow Diets - S. L. Bennett; Antonio Faciola (EDIS)
This report summarizes information on the usage of exogenous enzymes, such as their modes of action and effectiveness in lactating dairy cows. Written by S. L. Bennett and A. P. Faciola, and published by the UF/IFAS Department of Animal Sciences, March 2022.